Evaluation of the use of vermicompost on the crop production of two varieties of Pak choi (Brassica rapa var. chinensis) and on the soil structure in Suriname - RAMNARAIN, YVONNE INDRANI; ORI, LYDIA; ANSARI, ABDULLAH ADIL (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2017)
Ramnarain YI, Ori L, Ansari AA. 2017. Evaluation of the use of vermicompost on the crop production of two varieties of Pak choi (Brassica rapa var. chinensis) and on the soil structure in Suriname. Asian J Agric 1: 73-79. The present research was carried out from January to May 2016 at the Anton de Kom University of Suriname, Paramaribo. The investigation consisted of a field and laboratory study in order to evaluate the effect of vermicompost on crop production of 2 varieties Brassica rapa var. chinensis, white and green Pak choi, nutrient availability in the soil after the use of vermicompost and nutrient value of the crop.The experiment was carried out (completely randomized design) in a greenhouse for six weeks. The treatments were vermicompost (V), cow manure (S), chemical fertilizer (K) and control (C). Plant growth parameters were recorded during the experiment (plant height and number of leaves) and after harvest (root and shoot biomass, leaf area). Nutrient analysis (Ca and Fe) of Pak choi was also conducted followed by pre and post-experiment soil analysis (pH, EC, TOC, N, P, K and C/N ratio). The results were collected and analyzed using Sigma Plot 12.0 tools. In the white Pak choi the number of leaves, root length and weight of fresh plants showed no significant differences among the four treatments using Tukeyâ??s test (Pâ?¤0.05). In the green Pak choi the number of leaves and root length showed no significant differences among the four treatments by Tukeyâ??s test (Pâ?¤0.05). Furthermore, the soil parameters (pH, OC, N) did not indicate a significant increase or decrease of the elements in the soil. P did decrease significantly and K increase in the treatments in the soil was not relevant.The evaluation of the use of vermicompost on the crop production of 2 varieties of Pak choi (Brassica rapa var. chinensis) proved that the plants treated with vermicompost had similar results as those treated with cow manure and chemical fertilizer.